MANIPULATIVE COOPERATION POLITICS OF MLM COMPANIES IN SURABAYA CITY - Retno Andriati (Humaniora, 2015)
Many studies on multi-level marketing business from law, management, marketing economic and anthropology perspectives have been focused on its legality which is victims of MLM companies/fake MLM companies. Studies on market phenomenon and entrepreneurship of MLM large industry fromeconomy anthropology perspective are still rare especially in Indonesia. The study is intended to identify the underlying cooperation policy as well as manipulative conduct of MLM business in Surabaya.The study employs qualitative and ethnographic approaches. Qualitative data wereanalyzed using ethnographic approaches. The result of research suggests that MLM businesses have undertaken manipulative cooperation politics by establishing both international level direct selling association (WFDSA) and national association (APLI) in response to the MLM business controversy. APLI exploits andmanipulates non-member of APLI. Exploiting and manipulating MLM members through ideology doctrine and marketing plan of MLM business/corporate culture